ANALISIS PENGETAHUAN KEUANGAN, KEPRIBADIAN DAN SIKAP KEUANGAN TERHADAP PERILAKU MANAJEMEN KEUANGAN - Eni Puji Estuti; Ika Rosyada; Faridhatun Faidah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
bstract. The role of MSMEs is very dominant in Indonesia's economic growth. The existence and performance of SMEs that are increasingly stretched are not without problems and obstacles. There are several problems including in the financial management behavior of MSME actors. This study aims to analyze the effect of financial knowledge, personality, and financial attitudes on financial management behavior. The population in this study are all flower farmers who are members of the Memayu Jogo Tonggo Cooperative, Kopeng Village Getasan District, Semarang Regency. Data analysis used classical assumptions and multiple regression analysis, t test, F test and coefficient of determination. The results showed that the financial knowledge variable and personality variable had no effect on the financial management behavior variable. The Financial Attitude variable has a positive and significant effect on the Financial Management Behavior variable.